2019
DOI: 10.1530/rep-18-0476
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulation of spermatogonial stem cell renewal and differentiation

Abstract: The intricate molecular and cellular interactions between spermatogonial stem cells (SSCs) and their cognate niche form the basis for life-long sperm production. To maintain long-term fertility and sustain sufficiently high levels of spermatogenesis, a delicate balance needs to prevail between the different niche factors that control cell fate decisions of SSCs by promoting self-renewal, differentiation priming or spermatogenic commitment of undifferentiated spermatogonia (A undiff ). Previously the SSC niche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 117 publications
2
41
0
Order By: Relevance
“…The differentially expressed genes associated with stemness maintenance, proliferation and the cell cycle in both control and Prmt5 -deficient SSCs were examined by real-time PCR and western blot analysis. Plzf , Oct4 , Nanos3 , and Gfra1 are well-characterized pluripotent factors that are important for the maintenance of SSC stemness ( Oatley and Brinster, 2008 ; Chen et al, 2017 ; Mäkelä and Hobbs, 2019 ). As shown in Figure 5 , the expression of Prmt5 was dramatically reduced in Prmt5 flox /flox ;Cre-ER TM SSCs treated with 1 μM tamoxifen compared to those treated with ethanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentially expressed genes associated with stemness maintenance, proliferation and the cell cycle in both control and Prmt5 -deficient SSCs were examined by real-time PCR and western blot analysis. Plzf , Oct4 , Nanos3 , and Gfra1 are well-characterized pluripotent factors that are important for the maintenance of SSC stemness ( Oatley and Brinster, 2008 ; Chen et al, 2017 ; Mäkelä and Hobbs, 2019 ). As shown in Figure 5 , the expression of Prmt5 was dramatically reduced in Prmt5 flox /flox ;Cre-ER TM SSCs treated with 1 μM tamoxifen compared to those treated with ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…Spermatogonia contain a small population of germline-specific stem cells with the ability to self-renew and differentiation. The differentiation of spermatogonia is stimulated by both intrinsic and extrinsic factors, which subsequently generate differentiating spermatogonia, spermatocytes, spermatids, and mature sperm ( Chen and Liu, 2015 ; Mäkelä and Hobbs, 2019 ). In mammals, both genetic and epigenetic modifications are involved in the development of male germ cells.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some other markers of rodent spermatogonia and their progenitors may not be conserved in humans. For example, it remains to be explored whether certain markers of rodent spermatogonia such as RET [37], STRA8 [38], CDH1 [39], and NEUROG3 (NGN3) [40] are also present in human spermatogonia. Conversely, certain specific markers of human spermatogonia have not been observed in rodents.…”
Section: Characteristics Of Spermatogonia In Primatesmentioning
confidence: 99%
“…In mammals, SSCs lie on the basement membrane of the seminiferous epithelium and are in contact with Sertoli cells, which control the fate of the SSCs via physical and paracrine interactions [4,[29][30][31]. In addition to Sertoli cells, peritubular myoid cells and Leydig cells may contribute soluble growth factors to the niche environment [32][33][34]. Mammalian SSCs are preferentially located in those areas of the seminiferous tubules near the interstitial tissue where Leydig cells and blood vessels reside (Figure 3) [33,[35][36][37][38].…”
Section: Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…In addition to Sertoli cells, peritubular myoid cells and Leydig cells may contribute soluble growth factors to the niche environment [32][33][34]. Mammalian SSCs are preferentially located in those areas of the seminiferous tubules near the interstitial tissue where Leydig cells and blood vessels reside (Figure 3) [33,[35][36][37][38]. Recent studies have shown that type A undifferentiated spermatogonia are uniformly distributed on the basement membrane of seminiferous mouse epithelium [39].…”
Section: Spermatogonial Stem Cell Nichementioning
confidence: 99%